An assessment of wind energy potential of the Amatole district in the Eastern Cape Province of South Africa - Masukume, Peace-maker; Makaka, Golden; Tinarwo, David (Proceedings of SAIP 2013: 58th Annual Conference of the South African Institute of Physics, 2021)
South Africa is heavily depended on fossil fuels for its energy needs and is the highest emitter of greenhouse gasses in Africa and 18th in the world. It is therefore imperative to shift to renewable energy sources for power production to mitigate the carbon emissions. The purpose of this paper is to investigate wind energy potential in the Amatole District in the Eastern Cape Province of South Africa. The Weibull density function was used to estimate the wind energy potential in this location. The Weibull parameters, k(shape parameter) and c(scale parameter) varied from 1.651 to 2.026 and 3.093 to 4.310 respectively. The study shows that the area has moderate wind energy potential for decentralized wind energy systems, exploitable at 10m or more for low speed wind turbines. It therefore follows that it is not suitable for large scale wind energy production.